Adoption Potential for Conservation Agriculture in Africa: A Newly Developed Assessment Approach (QAToCA) Applied in Kenya and Tanzania. (26th December 2012) - Ndah, H. T.; Schuler, J.; Uthes, S.; Zander, P.; Triomphe, B.; Mkomwa, S.; Corbeels, M.
Abstract Conservation agriculture (CA) is often promoted as a set of cropping practices to reduce soil erosion and maintain soil fertility, while decreasing production costs and increasing crop yields. However, CA adoption is extremely low in Africa. Most investigations on constraints of its adoption leave out (i) the characteristics of CA as an emerging innovation and (ii) the wider institutional context. A comprehensive self‐assessment tool for a systematic evaluation of factors influencing the CA adoption process at the field, farm and regional scale in a variety of regional contexts in Africa is still lacking. In an attempt to fill this knowledge gap, this article presents the motivation, development and testing of a Qualitative expert Assessment Tool for CA adoption in Africa (QAToCA) and its application. QAToCA is directed to regional experts, research teams and managers of development projects with a focus on CA, and allows them to assess their CA activities along a systematic, expert‐based list of questions and criteria. Specifically, it aims at assessing the adoption potential of CA under the varied agro‐ecological, socio‐economic, cultural and institutional conditions of Africa as well as the specific supporting and hindering factors influencing this process. As an example, its application in Kenya and Tanzania identified a relatively high CA adoption potential. The following factors, however, are noticed to require further improvement: accessibility of markets for CA products and inputs; adaptation of machinery and seeds to the CA practices; introduction of quality implementation measures; and a renewed motivation (interest) among CA service providers. Copyright © 2012 John Wiley & Sons, Ltd.